Impact of a Cylinder Against a Rigid Target Part I. Compatibility Conditions and the Viscoplastic Region Evolution - Kosiński, W.; Nowińska, A. (Engineering Transactions, 1991)
In the paper the impact test of a short deformable cylinder against a rigid target is analysed in terms of the rigid viscoplastic model [1]. The one-dimensional analysis of that experimental configuration has been carried out by numerous authors, e.g., [2, 3, 41 5, 7]. In this paper the axi-symmetric geometry, radial inertia, and finite deformations are taken into account. The equations of motion together with the constitutive model lead to an initial moving boundary-value problem. The analysis of the field regularity on the moving rigid-viscoplastic boundary is the crucial point of the considerations. It leads to the conclusion that the initial discontinuous condition does not belong to the solution. The relationship describing the displacement velocity of the boundary is derived as a function of the process fields.